Living labs contributions to smart cities from a quadruple-helix perspective - Esashika, Daniel Shim de Sousa (2020)
This dissertation offers an assessment of the living labs\' contributions to smart cities from a quadruple-helix perspective presented in five chapters: introduction, three papers, and a conclusion. The first paper addresses the controversy over the definition of a smart city. In this sense, we offer a meta-synthesis of studies that revised smart cities\' concepts. There are five characteristics found in the literature to describe a smart city: a) advanced ICT technology; b) sustainability; c) innovative and high skilled society; d) high tech governance and citizen participation; and e) knowledge-based economy. The second paper addresses the different approaches to assessing smart cities. We carried out a systematic review of the literature to describe models for evaluating smart cities. Besides the rankings approach, highlighted in the academic literature and specialised media, we identified three other approaches: data-driven management, maturity level, and innovation ecosystems. Finally, in the third paper, we explore the living labs\' contributions to smart cities from a quadruple-helix perspective, the central aspect of this dissertation. We conduct exploratory case studies. The selected cases (Living Lab Florianópolis, Living Lab of the Itaipu Technological Park, and Porto Digital) are part of an institutional context characterised by a low interaction between the quadruple-helix components. The data were obtained through documentary analysis and interviews with the organisers and participants of the living labs. The results suggest that living labs can contribute by a) selecting the most promising projects to be promoted; b) connecting quadruple helix components through collaborative practices and events; c) facilitating mediation between participants in living labs and government agencies, universities, and local companies to conduct tests; and d) insertion of the fourth helix as a tester, but not as a co-creator. These results contradict the notion that living labs are based on user-oriented innovation processes and suggest a producer-oriented trajectory.